Comparative Study on Gono Gini's Assets Due to a Death according to the Islamic Law and Positive Law - Syafrudin, Pardan (Journal of Islamicate Studies, 2019)
The Common properties (community property) is an asset that the husband and wife acquired during the household life, which both of them is agree that after united through marriage bonds, that the property produced by one or both of them will be common property. It shows, that if there's an agreement between husband and wife before marriage (did not to unify their property), then the property produced both will not become a joint treasure. Thus, if a husband or wife dies, or divorces, then the property owned by both of them can be distributed in accordance with their respective shares, another case when the two couples are not making an agreement, then the property gained during marriage bonds can be divided into types of communal property. In Islamic law, this kind of treasure is not contained in the Qur'an or Sunnah. Nor in Islamic jurisprudence. However, Islamic law legalizes the existence of common property as long as it is applicable in a society and the benefit in the distribution of such property. In contrast to the positive law, this property types have been regulated and described in the Marriage Law, as well as the Islamic Law Compilations, which became the legal restriction in the affairs of marriage in force in Indonesia. In this study, the author tries to compile the existence of common property according to the Islamic law reviews and positive law.